Unilateral Sanctions under International Law and Effectiveness of Blocking - D. S. Boklan; V. V. Koval (Московский журнал международного права, 2024)
INTRODUCTION. This article discusses modern international legal concept of unilateral sanctions. The authors contribute to the emerging discussion on the qualifying of unilateral sanctions under international law.MATERIALS AND METHODS. In this study we took into account the works of both Russian and foreign scholars in the field of international economic law, as well as analyzed documents and materials of international organizations (United Nations (UN), World Trade Organization (WTO) and others) in order to assess the compatibility of unilateral sanctions with international law. General scientific methods of cognition (analysis, synthesis, induction, and deduction), special legal methods (formal-legal, technical-legal, method of legal analogy) and comparative legal method were used in the presented research.RESEARCH RESULTS. Presented analysis has shown that widely used term “unilateral sanctions” leads to abusive and inappropriate use of international legal term. Analysis of compatibility of unilateral sanctions with other types of coercive measures such as countermeasures, UN Security Council sanctions, retortions, reprisals have shown that unilateral sanctions do not fall under the meaning of all mentioned measures. In addition, unilateral sanctions should not be justified under the WTO security exceptions. The use of extraterritorial unilateral sanctions contradicts one of the fundamental principles of international law – principle of non-interference in internal affairs. Existing blocking unilateral sanctions mechanisms are not efficient enough to compensate negative effect posed by unilateral sanctions.DISCUSSION AND CONCLUSIONS. Authors concluded that unilateral sanctions in most of the cases do not satisfy cumulative criteria of legitimate countermeasure. Unilateral sanctions are not equivalent to the United Nation Security Council sanctions, as there are no “checks and balances” in the decision-making process in the form of determining the degree of threat to peace and security and taking into account humanitarian exceptions. Although there is some correlation between unilateral sanctions and retortions or reprisals, retortions and reprisals posses criteria of legality and proportionality, while, unilateral sanctions are introduced at the state’s discretion without any standard. Furthermore, the authors argue that to avoid abusive use of the WTO security exceptions WTO panels have to rely on the well-balanced approach used by the Panel in Russia – Transit case. This approach shows that the context of security exception should be understood as encompassing only military and closely related to military issues and does not cover political, economic, cultural or any other interests and relations. Existing blocking mechanisms of unilateral sanctions require separate qualification under international law including compatibility with the legitimate countermeasures.